Chromogenic detection of hydrogen sulfide using squarylium-based chemosensors - Noh, Ha Lim; Oh, Byeong M.; Park, Young Ki; Chun, Hye W.; Lee, Junyeop; Kim, Jae Keon; Zheng, Jian; Jung, Daewoong; Lee, Woosung; Kim, Jong H. (Spectrochimica Acta - Part A: Molecular and Biomolecular Spectroscopy, 2020)
Squarylium-based colorimetric hydrogen sulfide (H2S) chemosensors (SQ1, SQ2, and SQ3) were developed, and their detection properties were systematically characterized. SQ1 exhibited rapid and high resolution H2S sensing properties through significant color changes detectable by naked-eye with limit of detection as low as 7.2 ppb. SQ1 also showed excellent selectivity for H2S detection over other relevant anions and nucleophiles. Sensing mechanisms of SQ1 were investigated based on spectroscopic and 1H NMR analyses with quantum calculations. Furthermore, SQ1 showed an efficient response to H2S under versatile conditions in the solution, solid, and dyed fabric states, which suggests applicability of SQ1 to simple, low-cost, and practical H2S sensors.
Keywords: Chemo-sensors; Color changes; High resolution; Limit of detection; NMR analysis; Quantum calculation; Sensing mechanism; Sensing property; Colorimetric chemosensor; Hydrogen sulfide; Selectivity; Spectroscopic characterization; Squarylium derivative